2012
DOI: 10.5539/ibr.v5n9p89
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Organizational Culture and the Relationship between Transformational Leadership and Job Satisfaction in Petroleum Sector of Libya

Abstract: The purpose of this study is to investigate the effect of organizational culture on the relationship between transformational leadership and job satisfaction in petroleum sector with a focus on the National Oil Corporation of Libya (NOC). This research was carried out by measuring the data gathered from the five point Likert scale. The Multifactor Leadership Questionnaire (MLQ), Organizational Culture Assessment Instrument (OCAI) and Job Satisfaction Survey (JSS) were used. Quantitative survey method was appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 25 publications
(23 reference statements)
5
20
0
8
Order By: Relevance
“…Clan culture and hierarchical culture brings internal focus and integration. Hierarchical culture and market culture brings stability and control (Cameron & Quinn, 2011;Zahari & Shurbagi, 2012). Keeping an external focus with adhocracy culture and market culture allows the organizations to identify the opportunity in the market by offering innovative solutions with minimum risk.…”
Section: Organizational Culture and Entrepreneurial Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…Clan culture and hierarchical culture brings internal focus and integration. Hierarchical culture and market culture brings stability and control (Cameron & Quinn, 2011;Zahari & Shurbagi, 2012). Keeping an external focus with adhocracy culture and market culture allows the organizations to identify the opportunity in the market by offering innovative solutions with minimum risk.…”
Section: Organizational Culture and Entrepreneurial Orientationmentioning
confidence: 99%
“…To get entrepreneurially oriented, members within the organizational system interact with each other and their surroundings to learn from it. The thinking and cognition of each member is influenced by public and private world forming culture of the organization (Lakomski, 2001;Zahari & Shurbagi, 2012). Organizational culture also depends on the policies and operating procedure already set in the organization.…”
Section: Introductionmentioning
confidence: 99%
“…Pemimpin transformasional adalah pemimpin yang memotivasi pengikut melalui inspirasi (Zahari, 2012). Para pengikut yang ditawarkan tantangan dan dukungan pengembangan kepribadian, berwujud konsentrasi pada kualitas seperti ide-ide, nilai-nilai dan visi dalam upaya membangun hubungan baik dalam organisasi (Maulizar dkk., 2012).…”
Section: Pendahuluanunclassified
“…Previous studies in international business and organizational studies confirm the complexity of culture in the management of all forms of organizations (Johanson & Vahlne, 2003;Chevrier, 2003;Zahari & Shurbagi, 2012). A number of studies have been conducted and confirmed strong relationship among various organizational factors and culture (e.g.…”
Section: Introductionmentioning
confidence: 96%
“…A number of studies have been conducted and confirmed strong relationship among various organizational factors and culture (e.g. Swierczek & Onishi, 2003;Zahari & Shurbagi, 2012).…”
Section: Introductionmentioning
confidence: 99%